PELATIHAN PEMBUATAN JAMU JAHE MERAH INSTAN DI PASIE JAMBAK KOTA PADANG - Nova Syafni; Wiwik Hanifah; Ryan Fajri Kurniawan; Lili Fitriani; Suryati Suryati (Jurnal Hilirisasi IPTEKS, 2023)
The majority of the population in the Pasie Jambak area depends on fishing as their livelihood, which requires them to be in excellent physical condition to carry out their work. Red ginger is one of the most commonly found plants in the market and is known to have benefits in maintaining bodily stamina. Therefore, the Student Executive Board of the Faculty of Pharmacy, Andalas University, in collaboration with faculty members and students, conducted training in the production of instant red ginger herbal drinks with the aim of making it a convenient health beverage for the fishing community, suitable for consumption during their fishing trips. This training was attended by a large number of women residing in the vicinity of Pasie Jambak, Padang City. The training process consisted of several stages. The first stage involved an explanation of the benefits of red ginger, followed by the second stage, which was a practical session on the production of instant red ginger herbal drinks using red ginger rhizomes, sugar, and water. The subsequent stage focused on the packaging of the red ginger product and the proper method of preparing the beverage. The training activities concluded with a discussion session and the completion of questionnaires regarding the implementation of the training. The results of this training demonstrated that the participants were able to smoothly produce and package instant red ginger herbal drinks. The questionnaire results also indicated that overall, all participants were satisfied with the training activities. Therefore, it is expected that this training will provide significant benefits to the community in the Pasie Jambak area, helping to improve their health and offering a practical solution for fishermen who require good physical stamina to carry out their work.